CMTM7 recognizes an immune-hot tumor microenvironment and predicts therapeutic response of immunotherapy in breast cancer well - Jiang, Xingyu; Qian, Zhengtao; Chen, Yu; Zhou, Tao; Zhao, Can; Yin, Yongxiang (Frontiers in Genetics, 2022)
Breast cancer (BRCA) is a complex disease that leads to major mortalities and unsatisfactory clinical outcomes among women worldwide. CKLF-like MARVEL transmembrane domain-containing 7 (CMTM7) is a potential tumor suppressor and regulator of PD-L1, which has been found as a functional signature in considerable oncogenesis, progression, and therapeutic resistance via deletion and downregulation. In this research, triple-negative breast cancer (BRCA), a molecular subtype having a lower response to endocrinotherapy but a higher response to chemotherapy and immunotherapy, showed higher transcriptional levels of CMTM7. Moreover, CMTM7 positively correlated with immunomodulators, tumor-infiltrating immune cells (TIICs), and immune checkpoints in many independent datasets. Furthermore, in an immunotherapy cohort of BRCA, patients with high CMTM7 expression were more sensitive to immunotherapy, and the therapeutic predictive value of CMTM7 is higher than that of PD-1 and PD-L1. To sum up, CMTM7 correlated with an inflamed tumor microenvironment and identified immune-hot tumors, which can be a novel biomarker for the recognition of immunological characteristics and an immunotherapeutic response in BRCA.